Gamma‐Ray Detection Using Bi‐Poor Cs2AgBiBr6 Double Perovskite Single Crystals. Issue 8 (1st March 2021) - Zhang, Zheng; Cao, Da; Huang, Zhengjie; Danilov, Evgeny O.; Chung, Ching‐Chang; Sun, Dali; Yang, Ge
Abstract: Lead halide perovskites have recently attracted intensive attention as competitive alternative candidates of legacy compound materials CdTe, CdZnTe, and TlBr for high sensitivity energy‐resolving gamma‐ray detection at room temperature. However, the use of lead in these lead halide perovskites, which is necessary for increasing the stopping power of gamma radiation, poses a serious environmental concern due to the high toxicity of lead. In this regard, environmental‐friendly perovskite‐based gamma‐ray detector materials with key energy‐resolving capabilities are highly desired. Here, the gamma energy‐resolving performance of a new class of all‐inorganic and lead‐free Cs2 AgBiBr6 double perovskite single crystals (SCs) is reported. Two types of Cs2 AgBiBr6 SCs, prepared by Bi‐normal and Bi‐poor precursor solutions, respectively, have been grown. Their mobilities and response to gamma radiation are presented. Density of trap states in Bi‐poor Cs2 AgBiBr6 SCs (2.65 × 10 9  cm −3 ) is one order of magnitude lower than that in Bi‐normal Cs2 AgBiBr6 SCs (3.85 × 10 10  cm −3 ). Using laser‐induced photocurrent measurements, the obtained mobility–lifetime (μ–τ) product in Bi‐poor Cs2 AgBiBr6 SCs is 1.47 × 10 −3  cm 2  V −1, indicating their great potentials for gamma‐ray detection. Further, the fabricated detector based on Bi‐poor Cs2 AgBiBr6 SC shows response to 59.5 keV gamma‐ray with an energy resolution of 13.91%. Abstract : In this work, Cs2 AgBiBr6 double perovskite single crystals (SCs) are solution‐processed from Bi‐normal and Bi‐poor conditions, respectively. It is found that Cs2 AgBiBr6 SCs grown from Bi‐poor conditions have enhanced mobility–lifetime product for charge carriers with high moisture/air stability and less material defects. In addition, Bi‐poor Cs2 AgBiBr6, as a promising semiconductor detector material, shows response to 59.5 keV gamma‐rays.